2014
DOI: 10.1016/j.otsr.2014.09.011
|View full text |Cite
|
Sign up to set email alerts
|

The human acromion viewed from an evolutionary perspective

Abstract: The high prevalence of rotator cuff tendinopathy in modern humans may be partly related to the shape acquired by the scapula as species changed throughout evolution. Here, we compared the anatomic features of the scapula across members of the Hominoid group. The results support the hypothesis that the scapula of Homo sapiens sapiens exhibits distinctive anatomic characteristics compared to that of other Hominoids. We studied 89 scapulae from five species. For each scapula, we measured eight parameters and dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 17 publications
1
13
1
3
Order By: Relevance
“…Moreover, the modified extension of the lateral acromial length accommodated for the attachment of the deltoid muscle which then counterbalanced the comparative weakness of the supraspinatus muscle. 21,22 This was consistent with the anatomical findings of Sakoma et al 23 who reported that the anterior, middle and posterior deltoid portions originated from the respective aspects of the lateral acromial length. Furthermore, in the recent study conducted by Viehö fer et al, 24 the lateral acromial length was reported to cause a change in the size of the deltoid moment arm and ultimately glenohumeral stability.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, the modified extension of the lateral acromial length accommodated for the attachment of the deltoid muscle which then counterbalanced the comparative weakness of the supraspinatus muscle. 21,22 This was consistent with the anatomical findings of Sakoma et al 23 who reported that the anterior, middle and posterior deltoid portions originated from the respective aspects of the lateral acromial length. Furthermore, in the recent study conducted by Viehö fer et al, 24 the lateral acromial length was reported to cause a change in the size of the deltoid moment arm and ultimately glenohumeral stability.…”
Section: Discussionsupporting
confidence: 88%
“…Nevertheless, previous theories about acromio-humeral distance have been questioned. Indeed, it is unclear if the height of the subacromial space really plays a role, as it is now considered as a neo-articulation—the permanent contact between the humeral head and coraco-acromial arch during elevation of the arm being normal [ 16 ]. There is also growing evidence suggesting that distinct scapular morphologies and not simply subacromial impingement may accelerate the underlying degenerative process [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The acromion partly covers the humeral head: it articulates with the clavicle and gives attachment to the anterolateral portion of deltoid and coracoacromial ligament. Its association with chronic pain and shoulder dysfunction has been observed (Voisin et al, 2014;Nyffeler & Meyer, 2017). The morphometry of the acromion process is important as it is related to pectoral girdle pathologies (Saha & Vasudeva, 2017).…”
Section: Introductionmentioning
confidence: 99%